The Learning Achievement and Analytical Thinking Ability Using Inquiry-Based Learning 7e With Gallery Walk Techique in Chemistry of Mathayomsueksa 4 Studens - Nantana, Wanida; Phetsuk, Phadung (Journal of Modern Learning Development, 2024)
The purposes of this research are to 1) compare the learning achievement in chemistry of mathayomsueksa 4 students using inquiry-based learning 7E with gallery walk technique between pretest and posttest. 2) compare the learning achievement in chemistry of mathayomsueksa 4 student using inquiry-based learning 7E with gallery walk technique between posttest with 75% of the total score. 3) compare the analytical thinking ability of mathayomsueksa 4 students using inquiry-based learning 7E with gallery walk technique between pretest and posttest. 4) compare the analytical thinking ability of mathayomsueksa 4 student using inquiry-based learning 7E with gallery walk technique between posttest with 75% of the total score. The research design employed is pre-experimental research using the one group pretest posttest design. The sample size was 34 students of the academic year 2023 in Mathayomsueksa 4 at Matthayom Si Samphaolun School, Bua Chet District Surin Province. by Cluster Random Sampling with the classroom serving as the base for random selection. The research instruments were 1) the lesson plans using inquiry-based learning 7E with gallery walk technique, 2) an achievement test and 3) an analytical thinking abilities test. The statistical methods used for data analysis were Mean, Percentage, Standard Deviation, and the t-test. The results of the research indicate that: 1) The learning achievement in chemistry of mathayomsueksa 4 students using inquiry-based learning 7E with gallery walk technique posttest was significantly higher than pretest at 0.05 statistical level. 2) The learning achievement in chemistry of mathayomsueksa 4 students using inquiry-based learning 7E with gallery walk technique posttest was significantly higher than 75% of the total score at 0.05 statistical level. 3) The analytical thinking ability in chemistry of mathayomsueksa 4 students using inquiry-based learning 7E with gallery walk technique posttest was significantly higher than pretest at 0.05 statistical level. and 4) The learning achievement in chemistry of mathayomsueksa 4 students using inquiry-based learning 7E with gallery walk technique posttest was significantly higher than 75% of the total score at 0.05 statistical level.